Fracture toughness of the vacuum-heat-treated spring steel 51CrV4 - Senčič, Bojan (Materiali in tehnologije, 2011)
In the work the possibilities of the vacuum heat treatment of spring steel grade 51CrV4 are presented. Charpy-V notch (CVN) impact-test values are widely used in toughness specifications for spring steels, even though the fracturing energy is not directly related to the spring design. The plain-strain stress-intensity factor (KIc) at the on set of unstable crack growth can be related to the spring design; however, KIc values are not used in the toughness specifications. This is surprising since to the designer KIc values are more useful than CVN values, because the design calculations for springs from high-strength steels should also take into account the strength and the toughness of materials to prevent rapid and brittle fracture. An investigation was conducted to determine whether standardized fracture-toughness testing (ASTM E399-90), which is difficult to perform reliably for hard and low ductility materials, could be replaced with a non-standard testing method using circumferentially notched and fatigue-precracked tensile specimens. The results of this investigation have shown that using the proposed method it was possible to draw, for the normally used range of working hardness, combined tempering diagrams (Rockwell-C hardness - Fracture toughness KIc - Tempering temperature) for the vacuum-heat-treated spring steel grade 51CrV4. Fractographic and metallographic analyses of the KIc-test specimens used shows in steel the presence of positive and negative segregations. It was found that the width of the segregations bands and the distance between the positive and negative segregations influence significantly the fracture toughness due to the presence of bainite in the negative segregations.
Keywords: vzmetno jeklo; vakuumska toplotna obdelava; trdota; lomna žilavost; mikrostruktura